Career Choices among Nursing Students: Differences between Freshmen and Interns - Sari, Ni Putu Wulan Purnama (JURNAL PENDIDIKAN KEPERAWATAN INDONESIA, 2020)
ABSTRACTCareer selection is one of the most important decisions that an individual makes in his life and is a core task of the late stages of adolescent development in the process of developing self-identity. This study aimed to describe the career choices of nursing students and analyze the differences between freshmen and interns. This cross-sectional study involved 110 and 66 freshmen and interns respectively in two private nursing colleges with â€œBâ€ accreditation predicate (n=176). Questionnaire of Survey on Career Choice was used in data collection. Descriptive statistic test was used in data analysis. Results showed that most freshmen chose two career choice alternatives (38.18%), but most interns were determined to choose only one alternative (42.42%). There were two most popular career choices among nursing students, such as: nurse practitioner (45.45% totally) and continuing education to be a Master/Specialist of Nursing (33.52% totally). The career intention to be a nurse practitioner in most respondents was referred to civil servant, both in clinical or community work places (59.66% totally). The most popular nursing fields were pediatric nursing in freshmen and psychiatric nursing in interns (34.55% and 25.76% respectively). Strengthening the attitude of love for nursing profession needs to be fostered early in the beginning of college life, so that career choice as a nurse practitioner after finishing the internship program can be maintained. Â Â Â ABSTRAKPemilihan karir adalah salah satu keputusan terpenting yang dibuat individu dalam hidupnya dan merupakan tugas inti dari tahap perkembangan remaja akhir dalam proses pembangunan identitas diri. Penelitian ini bertujuan mendeskripsikan pilihan karir mahasiswa keperawatan dan menganalisis perbedaannya di antara mahasiswa baru dan program Profesi Ners. Penelitian cross-sectional ini melibatkan 110 maba dan 66 mahasiswa profesi yang berasal dari dua institusi keperawatan terakreditasi B (n=176). Kuesioner Survey on Career Choice digunakan dalam pengumpulan data. Uji statistika deskriptif digunakan untuk menganalisis data. Hasil menunjukkan mayoritas maba memilih dua alternatif pilihan karir (38.18%), sedangkan mahasiswa profesi Ners mantap memilih satu pilihan saja (42.42%).Â  Terdapat dua jenis pilihan karir yang populer pada mahasiswa keperawatan, yaitu sebagai perawat praktisi (total 45.45%) dan studi lanjut untuk menjadi Magister/Spesialis Keperawatan (total 33.52%). Intensi karir sebagai perawat praktisi pada mayoritas responden mengarah pada menjadi Pegawai Negeri Sipil (PNS), baik di tatanan klinik maupun komunitas (total 59.66%). Bidang Keperawatan Anak paling populer di kalangan maba (34.55%), sedangkan bidang Keperawatan Jiwa paling populer di kalangan mahasiswa Profesi Ners (25.76%). Penguatan sikap kecintaan terhadap profesi perawat perlu dipupuk sejak dini di awal masa kuliah agar pilihan karir sebagai perawat praktisi pasca lulus dari program Profesi Ners dapat dipertahankan. Â Â Â